Efficacy of the Santhiflex™ method of psychomotor postural re-education in the treatment of chronic low back pain - Olívia Santos Pereira
Introduction Chronic low back pain is conceived of as a multifactorial syndrome that results in the loss of functional capacity. It affects the quality of life of an individual and its treatment requires a comprehensive therapeutic approach. Objective The aim of this study is to assess the efficacy of the Santhiflex™ Method in the treatment of chronic low back pain, as well as its effects on functional capacity, health-related quality of life and body posture. Materials and methods 20 patients with chronic low back pain were randomly distributed into two groups of 10: an experimental group, which was treated with the Santhiflex™ Method of psychomotor postural re-education; and a control group, which was given a lecture on postural orientation after the first evaluation. Results The obtained data were analyzed using standard statistical software, SPSS-17 for Windows (SPSS, Chicago, IL, USA) and the results were expressed as absolute and relative frequencies, and median with first and third quartiles. The nonparametric Wilcoxon test was used for within-group samples. Intergroup comparison was performed using the Mann-Whitney test. A value of p < 0.05 was considered statistically significant. There were significant differences in the main factors assessed. Discussion The findings demonstrated a significant total improvement in low back pain scores in the EG, whereas there was no significant change in the CG. Conclusion The Santhiflex™ Method is effective in the treatment of low back pain and has positive effects on functional capacity and health-related quality of life.